Prices versus quantities in electricity generation - Mark Hahmeier (Max Planck Institute for Research on Collective Goods, 2009)
This paper examines the prices versus quantities issue, originally raised by Weitzman [8], in the context of carbon dioxide emissions and with a special focus on electricity generation. Within a simpli ed model of the electricity market, in which we explicitly allow for a monopolistic gas supplier, we employ a game-theoretic approach and ask, from a welfare perspective, for the superior regulatory regime in response to an expected exercise of market power. Our analysis studies the optimal regulation in each regime and shows that, in the presence of market power in the gas market, taxes rather than permits are the regulator's welfare-maximizing regime choice.
Keywords: H23; L51; L94; Q54; Q58; 330; Climate change; regulation; taxes; emission permits; market power; gas; welfare